Dioxomolybdenum(VI) Complexes of Methylpiperidine Dithiocarbamates - SOVILJ, S.P.; MITIC, D.; LEOVAC, V.M. (Asian Journal of Chemistry, 2010)
Three new complexes of dioxomolybdenum(VI) of the general formula [MoO2(Rdtc)2], where Rdtc- refer to 2-, 3- or 4- methylpiperidine (2-, 3-, 4-Mepipdtc) dithiocarbamates, have been prepared. The complexes have been characterized by elemental analysis, conductometric measurements, electronic, IR and NMR spectroscopy. Through contributions of resonance structures which lead to an effective dianion electronic structure the two dithiocarbamate ions join with both the sulphurs to the molybdenum atom. The complexes contain a cis-MoO2 group and are of octahedral geometry. The position of the methyl group on the piperidine ring has influence on the v(C'-'-'N) and v(C'-'-'S) vibrations which decrease in the order 2-Mepipdtc> 3-Mepipdtc > 4-Mepipdtc.